Assessment of Teaching Modules as Physics Teachers' Review of Ethnoscience Issues in the Context of Rebana - Nasution, Nabila Nur Almaida; Santoso, Irsyad Yusuf; Habibi, H; Hidaayatullaah, Hasan Nuurul; Putri, Pretty Oktianti Menur Kusuma (National Dong Hwa University, 2024)
This study aims to assess an ethnoscience-based physics learning module in the context of rebana from the perspective of science and engineering teachers, focusing on the relevance of scientific content to local culture, the dimensions of scientific literacy, and the module's contextual appeal and associated challenges. Employing a mixed-methods approach with an explanatory design, the study began with the collection of quantitative data using a Likert-scale instrument administered to 40 purposively selected respondents, followed by in-depth interviews to explore contextual ethnoscience issues and the types of support needed. The results indicated that most respondents provided highly positive feedback on the integration of physics content with ethnoscience, evaluating the module as an effective and engaging learning tool. However, challenges persist, particularly regarding teachers’ limited understanding, lack of relevant learning resources, and the difficulty of connecting local culture with abstract scientific concepts. Therefore, support in the form of professional development, the creation of contextual learning media, cross-sector collaboration, and adaptive educational policies is essential to ensure the effective and sustainable implementation of ethnoscience-based physics learning.